Complementary Honey Therapy To Reduce The Frequency Of Diarrhea In Toddlers: Literature Review - Puspita , Uci Nurhayati; Muhith, Abdul; Zahro, Chilyatiz (Journal of Applied Nursing and Health, 2023)
Background: Diarrhea is a major health problem in children that still occurs frequently and even has the potential to become an outbreak (extraordinary event), which is often accompanied by death due to the release of fluid from the body caused by bacteria and causing dehydration in children. This literature review aims to determine the effect of honey complementary therapy on reducing the frequency of diarrhea in toddlers. Methods: The method used in this article is a literature review using journal databases from Google Scholar, Pubmed, and Science Direct in the 2020-2023 period with the keywords "Diarrhea," "Honey Therapy," and "Children," resulting in 1,637 articles. Results: Articles were selected according to the criteria, and the result was 15 articles ready to be reviewed. Providing complementary therapy with honey influences the frequency of diarrhea in children by giving it 3x5ml per day as long as the child has diarrhea until the frequency of diarrhea decreases. Conclusion: This literature review shows that giving complementary honey therapy to children can reduce the frequency of diarrhea by inhibiting the growth and development of bacteria in the digestive system, helping to replace lost body fluids